beta-Adrenoceptor agonists enhance 5-hydroxytryptamine-mediated behavioural responses. - Cowen, P; Grahame-Smith, D; Green, A; Heal, D (1982)
The beta-adrenoceptor agonists, salbutamol, terbutaline and clenbuterol, were investigated for their effect on 5-hydroxytryptamine-mediated (5-HT) hyperactivity. 2 The lipophilic beta-adrenoceptor agonist, clenbuterol (5 mg/kg) enhanced the behaviours induced by quipazine (25 mg/kg), including headweaving, forepaw treading and hind-limb abduction and thus increased automated activity recording. Clenbuterol (5 mg/kg) also enhanced the hyperactivity syndrome produced by the 5-HT agonist, 5-methoxy N,N-dimethyltryptamine (2 mg/kg) and the combination of tranylcypromine (10 mg/kg) and L-tryptophan (50 mg/kg). Salbutamol and terbutaline potentiated quipazine-induced hyperactivity only when given at the higher dose of 20 mg/kg. 3 The effect of clenbuterol in enhancing quipazine hyperactivity was blocked by the centrally acting beta 1-adrenoceptor antagonist, metoprolol (5 mg/kg), but not by the beta 2-adrenoceptor antagonist, butoxamine (5 mg/kg) or the peripherally acting beta 1-adrenoceptor antagonist, atenolol (5 mg/kg). 4 Clenbuterol (5 mg/kg) did not enhance the circling responses produced by methamphetamine (0.5 mg/kg) in unilateral nigrostriatal-lesioned rats. 5 The results suggest that beta-adrenoceptor agonists in common with some established antidepressant treatments produce enhancement of 5-HT-mediated behavioural responses.